Acceptability of Moringa Leaves Flour Mix Food as Complementary Food Supplement for Breastmilk - Esse Puji Pawenrusi; Kamariana Kamariana; Ernayulianti Ernayulianti (Indonesian Journal of Global Health Research, 2022)
Moringa leaf flour is well consumed as daily food supplement to overcome malnutrition on infants because has rich nutrient as a result of proteins, β carotene, calcium, iron and magnesium. This study aimed to recognize the acceptability of mixed food ingredients flour on Moringa leaves as complementary supplement of breast milk. This was quasi experimental research with nonequivalent control group design. We prepared a mixed food formula with red rice flour, breast milk or formula and olive oil. Then, determining the content of nutrients, food safety and acceptance of food complementary to mixed food ingredients formulation with 4 treatment of moringa flour consisted of (5 gram, 6 gr gram, 7 gram and 8 gram). The results revealed that the highest scores of all aspects (taste, texture, aroma and color) then formula one (F1) with the amount of addition of 5 gr of moringa flour is at the first sequence. The most formula contained was Calcium, Carbohydrate and protein that was in formula 1 with the amount of calcium by 8915.04 µg/g, carbohydrate by 18.57% and protein by 4.25%. on the other hand, formula 3 contained lots of fats by 2.25%.